Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol

Biocatalyst mediated production of 6 beta,11 alpha-dihydroxy derivatives of 4-ene-3-one steroids - Kolet, Swati P.; Niloferjahan, Siddiqui; Haldar, Saikat; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (Steroids, 2013)
Biotransformation of steroids with 4-ene-3-one functionality such as progesterone (I), testosterone (II), 17 alpha-methyltestosterone (III), 4-androstene-3,17-dione (IV) and 19-nortestosterone (V) were studied by using a fungal system belonging to the genera of Mucor (M881). The fungal system efficiently and quantitatively converted these steroids in regio- and stereo-selective manner into corresponding 6 beta,11 alpha-dihydroxy compounds. Time course experiments suggested that the transformation was initiated by hydroxylation at 6 beta- or 11 alpha-(10 beta-hydroxy in case of V) to form monohydroxy derivatives which upon prolonged incubation were converted into corresponding 613,11oc-dihydroxy derivatives. The fermentation studies carried out using 5 L table-top fermentor with substrates (I and II) clearly indicates that 6 beta,11 alpha-dihydroxy derivatives of steroids with 4-ene-3-one functionality can be produced in large scale by using M881. (C) 2013 Elsevier Ltd.
Keywords: 4-Ene-3-one steroids; Biotransformation; Mucor sp.

Biotransformation of vinblastine to vincristine by the endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Ahmad, Absar (Biocatalysis and Biotransformation, 2013)
A fungal transformation method for the production of the less abundant but more valuable anticancer drug vincristine using the more abundant anticancer drug vinblastine by an endophytic fungus Fusarium oxysporum isolated from the plant Catharanthus roseus is described. Vinblastine dissolved in sterile water when incubated with the fungal mycelial mass was transformed into vincristine at room temperature. The biotransformation process was monitored by periodic sampling of aliquots that were extracted with ethyl acetate. The crude transformed compounds were analysed using TLC where the Rf value of the spot obtained on the 8th day was found to be similar to that of standard vincristine (Rf 0.74). Purification by HPLC using a C 18 symmetry column showed a peak with RT (34.9 min) similar to that of standard vincristine. Further characterization with the help of ESI-MS showed a peak at m/z 825 attributed to the (M + H)(+) ion. This indicated that the fungus Fusarium oxysporum had converted vinblastine to vincristine.
Keywords: Biotransformation; endophytes; fusarium oxysporum; Vinblastine; vincristine

Phase, size and shape transformation by fungal biotransformation of bulk TiO2 - Khan, Shadab Ali; Ahmad, Absar (Chemical Engineering Journal, 2013)
Nanosynthesis is an ever expanding frontier in recent years in view of its implications to many future technologies covering diverse fields. Considerable progress has been made realizing high quality synthesis of elemental nanomaterials as well as compounds as chemical, biological and physical routes. The issue of technologically viable large scale synthesis still continues to be a challenge. Here we demonstrate a novel environmentally friendly top down approach to nanosynthesis which exploits the strength and peculiarities of fungus based bioleaching in extracting radicals from compounds and then providing them with a reactive as well as capping environment. Thus protein capped nanoparticles of TiO2 (5-28 nm, circular and brookite phase) are formed directly from micron size (150-250 nm, disc shape, anatase phase) powder by exposing them to a medium of fungus Humicola sp. at just 50 degrees C. The fungus Humicola sp. is not only useful for the synthesis of nanoparticles but also for the transformation of shape, phase and size of TiO2. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Anatase; Biotransformation; Brookite; humicola sp; TiO2

Fungi mediated production and practical purification of (R)-(-)-3-quinuclidinol - Kolet, Swati P.; Jadhav, Dipesh D.; Priyadarshini, Balaraman; Swarge, Bhagyashree N.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2014)
A fungal system belonging to Mucoraceae family (Mucor piriformis) was explored for the asymmetric reduction of a prochiral ketone, 3-quinuclidinone (I) in an efficient manner to produce an important pharmaceutical precursor (R)-(-)-3-quinuclidinol (II) with similar to 96% enantiomeric excess. The efficiency of the process was improved by developing a cation exchange resin (Amberlite IR-120) which assisted the purification of water soluble metabolite II from fermentation media. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R)-(-)-3-Quinuclidinol; Amberlite IR-120; Biotransformation; Ion exchange resin; Mucor pinformis

Mucor hiemalis mediated 14 alpha-hydroxylation on steroids: In vivo and in vitro investigations of 14 alpha-hydroxylase activity - Kolet, Swati P.; Haldar, Saikat; Niloferjahan, Siddiqui; Thulasiram, Hirekodathakallu V. (Steroids, 2014)
Transformation of testosterone and progesterone into synthetically challenging 14 alpha-hydroxy derivatives was achieved by using fungal strain Mucor hiemalis. Prolonged incubation led to the formation of corresponding 6 beta/7 alpha,14 alpha-dihydroxy metabolites. The position and stereochemistry of newly introduced hydroxyl group was determined by detailed spectroscopic analyses. The time course experiment indicated that fungal strain initiated transformation by hydroxylation at 14 alpha-position followed by at 6 beta- or 7 alpha-positions. Studies using cell-free extracts suggest that the 14 alpha-hydroxylase activity is NADPH dependent and belongs to the cytochrome P450 family. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: 14 alpha-Hydroxylase; Biotransformation; Mucor hiemalis; Progesterone; Testosterone

Chloroperoxidase applications in chemical synthesis of industrial relevance - Bhandari, Yogesh; Sajwan, Hemlata; Pandita, Parul; Koteswara Rao, Vamkudoth (Biocatalysis and Biotransformation, 2023)
Biocatalysts can accelerate the catalysis of a chemical reaction that is difficult to synthesize with typical chemical methods. The global enzyme market size is predicted to expand at a CAGR of 6.5% from 2021 to 2028. Enzymatic reactions are highly chemo, regio, and stereoselective and produce various fine chemicals such as drugs, agrochemicals, and fragrance molecules. Peroxidases (PO) (EC 1.11.1.x) are a large class of enzymes that play an important role in various biological processes. Chloroperoxidase (CPO, EC 1.1.1.10) is a versatile fungal haem-thiolate protein that is useful in the asymmetric synthesis of chiral building blocks and has an important role in a number of biological processes. CPO's main biological role is chlorination, although it also catalyses haem PO, catalase (CAT), and reactions similar to cytochrome P450. However, CPO performs both oxidation and stereo-specific halogenation of chemical molecules. The haem and vanadium POs are produced by Caldariomyces fumago, and Curvularia inaequalis, respectively, and are capable of halogenating the flavanones, naringenin, and hesperetin, at C-6 and C-8 in the presence of either Cl- or Br-. In this review, we discussed the various applications of CPO including synthesis of epoxides, drugs, halogenation of thymol, nitriles, the Aza-Achmatowicz reaction, and biomedical applications such as cancer and biosensors. In light of these novel features, we have provided a detailed review of CPOs and their applications in various stereoselective chemical transformations of industrial relevance.
Keywords: active pharmaceutical ingredients; Biotransformation; Caldariomyces fumago; chemo; Chloroperoxidase; regio; stereoselectivity